(untitled) (Nigerian Journal of Technology, 2016)
An assessment of rice production and processing in South-Eastern Nigeria was carried out by investigative survey approach. The survey was basically to ascertain the extent of mechanization applicable in the area to enable the agricultural policy makers device the modalities for improving rice production and processing in the area. According to the results obtained from the study, the planting period of rice in the area was mostly between May and August. Virtually 77% of the farmers raise the rice seedlings in the nursery bed before transplanting to the permanent seed bed while 23% sow the seeds directly to the seed bed where they germinate and grow to maturity. Results revealed that 75% of the farmers in the South-Eastern Nigeria use manual labour in the seed bed preparation while 25% use tractors. It was observable from the results that 15-15-15 NPK and urea fertilizers were predominantly used by the farmers in the area for rice production and the application method was mostly by manual broad casting over the planted area. Results also recorded that rice harvesting mostly took place from October – December; and about 69% of the farmers harvest their rice manually while 31% use mechanical means. More so, average of 49.6% of the farmers thresh their harvested rice manually while 50.4% of them use mechanized means. It was also observed that 93% of the farmers use both steam heating and total drenching method in parboiling the paddy rice while 3.4% and 3.6% use steam heating and total drenching respectively in parboiling the paddy rice. The milling method applicable in the area was mainly by mechanical means with 73.6% of the farmers who use the method while 10.4% of the farmers use manual method. The farmers generally use sacks in bagging and/or storing both the paddy and milled rice. Finally results showed that mechanization of rice production and processing has not received much attention as most of the farmers still use manual labour and traditional approach in the production and processing of rice. http://dx.doi.org/10.4314/njt.v36i1.27